1999
DOI: 10.1354/vp.36-3-212
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of 1,3,5-Trinitrobenzene (TNB): Immunohistochemical Study of Cerebrovascular Permeability

Abstract: Abstract. 1,3,5-Trinitrobenzene (TNB) is a soil and water contaminant at certain military installations. Encephalopathy in rats given 10 daily oral doses of TNB has been reported. The lesion was bilaterally symmetric vacuolation and microcavitation in the cerebellar roof nuclei, vestibular nuclei, olivary nuclei, and inferior colliculi. The contribution of the blood-brain barrier (BBB) in the genesis of these lesions remains uncertain. One of the main goals of the present work was to evaluate the functional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Prior to the tissue lesion, however, TNB breaks down the BBB and allows large serum proteins to diffuse through it. Thus, the selective regional vulnerability of brain capillaries to TNB has been suggested as a critical event in TNB-mediated neurotoxicity (5). Other nitrobenzene derivatives such as m-dinitrobenzene share similar toxic mechanisms by provoking oxidative cytotoxicity of the BBB, followed by neuronal and neuroglial injury (6).…”
Section: Neurotoxicity Due To Injured Barrier Structures: Nitrobenzenmentioning
confidence: 99%
“…Prior to the tissue lesion, however, TNB breaks down the BBB and allows large serum proteins to diffuse through it. Thus, the selective regional vulnerability of brain capillaries to TNB has been suggested as a critical event in TNB-mediated neurotoxicity (5). Other nitrobenzene derivatives such as m-dinitrobenzene share similar toxic mechanisms by provoking oxidative cytotoxicity of the BBB, followed by neuronal and neuroglial injury (6).…”
Section: Neurotoxicity Due To Injured Barrier Structures: Nitrobenzenmentioning
confidence: 99%
“…Immunohistochemical staining of excised brains was used to evaluate the integrity of the blood-brain barrier in F344 rats challenged with TNB [22]. Five male F344 rats/group were gavaged with TNB in corn oil at 71 mg/kg for 4, 5, 6, 7, 8, or 10 days with 1 dose per day.…”
Section: Mammalian Oral Toxicity: Subacutementioning
confidence: 99%
“…TNB is a soil and water contaminant at installations that are currently or have been involved in the manufacture of explosives. Previous studies in Fischer-344 rats receiving single daily oral doses of trinitrobenzene over 6 to 10 days have resulted in methemoglobinemia, hemolytic anemia, testicular atrophy, and neurologic pathology (Chandra 1995;Chandra, Qualls, and Reddy 1995a;Chandra et al 1997a;Chandra, Qualls, and Reddy 1997b;Chandra et al 1999). Ataxia progressing to recumbence is a manifestation of the neurologic abnormalities.…”
mentioning
confidence: 99%
“…The mechanisms by which TNB exerts its toxic action on the central nervous system (CNS) are unclear, but previous investigators have shown that TNB-mediated tissue damage is accompanied by breakdown of the blood-brain barrier (BBB) with extravasation of albumin (Chandra et al 1999). Astrocytes contribute to the maintenance and induction of the BBB characteristics in the brain endothelium, including tightness of tight junctions (Stewart and Wiley 1981; Butt, Jones, and Abbott 1990; Rubin et al 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation